2021
DOI: 10.1021/acs.analchem.1c00470
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Strategy for Constructing Ratiometric Upconversion Luminescent Probe with Sensitized Emission of Energy Acceptor

Abstract: When fabricating ratiometric optical probes using lanthanide-doped upconversion nanoparticles (UCNPs), which are promising luminescent materials that have widely been utilized in biosensing and bioimaging as energy donors, it is still a challenge to obtain the emission signal of energy acceptors with reasons unclear so far. Herein, we reveal that the energy-transfer efficiency and brightness of UCNPs as well as the aggregation-caused quenching (ACQ) of energy accepting dyes are the main factors restricting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Thus, a unique type of ratiometric UCL nanoprobes can be constructed by plotting a functioning relationship of the "U/F" or "F/U" ratio vs. target concentration (or the condition). [88][89][90][93][94][95]99,106,140,149,155,159,162 During the practical process of sensing applications, to acquire highly sensitive ratiometric UCL signal outputs in response to targets, the changes in U 1 /U 2 ratiometric values in the presence of targets should be remarkable enough, while very small changes in target concentration (condition) can be effectively distinguished through observable changes in U 1 /U 2 ratiometric values. In the well-plotted linear relationship of U 1 /U 2 vs. the target concentration (Scheme 2b), there is enough large positive slope.…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
“…Thus, a unique type of ratiometric UCL nanoprobes can be constructed by plotting a functioning relationship of the "U/F" or "F/U" ratio vs. target concentration (or the condition). [88][89][90][93][94][95]99,106,140,149,155,159,162 During the practical process of sensing applications, to acquire highly sensitive ratiometric UCL signal outputs in response to targets, the changes in U 1 /U 2 ratiometric values in the presence of targets should be remarkable enough, while very small changes in target concentration (condition) can be effectively distinguished through observable changes in U 1 /U 2 ratiometric values. In the well-plotted linear relationship of U 1 /U 2 vs. the target concentration (Scheme 2b), there is enough large positive slope.…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
“…The normalized data indicated that the H 2 S level in HCT-116 cells was approximately 4-5 folds higher than that of MCF-7 cells (Figure 5B), which was in agreement with the previously reported H 2 S concentration measured using a ratiometric H 2 S probe. 41 The differentiation of tumor type was further conducted at living-body level. HCT-116 tumor-bearing mice with high H 2 S expression and MCF-7 tumor-bearing mice with low H 2 S expression were selected for tests.…”
Section: The Ability Of Wh-n 3 To Differentiate Tumor Typesmentioning
confidence: 99%
“…When the concentration of H 2 S n decreased, SiR2 released H 2 S n and returned to SiR1, accompanying with the recovery of absorption and weakened UCL. In this process, the green UCL emission at 545 nm showed a slighter change than the red UCL emission because of the interrelation between these two UCL emission peaks, , which can be utilized as an internal standard signal for constructing a ratiometric probe to eliminate the interferences caused by the uneven distribution of probes and variations of the biological environment and instrument. , With the as-prepared nanoprobe, we can dynamically monitor the concentration changes of H 2 S n in living cells and mice.…”
Section: Introductionmentioning
confidence: 99%